ISOLASI LIGNIN DARI LINDI IUTAM (The Isolation of Lignin from Black Liquor) - Gustan Pari (Jurnal Penelitian Hasil Hutan, 1990)
At  the present  investigation two  lignins taere prepared for  the comparison of physicochemical properties. One represent«a lignin o'f)tained by evapomtion and the other represents a lignin isolated by precipitation.For each treatment, the, lignin products was refluxed  by ethanol, hot  water and unrefluxed.The result shows that the yield of lignin mnges from 21,9838,21  percent, ash content from 29,3151.,83 percent, silica content from 15,4027,71   percent moisture content from 3,198,09,   methoxyl  content from 0,912,64  percent, pH from  4,015,09   phenol content from 2,147,52   percent, surface area from 29,042,0   m1/gr, lignin content from 67,1180,16  percent and equivalent weight rangesfrom 2512,545277,  78.